Sustainability aspects of food and drinks offered in vending machines at Slovenian universities - Rozman, Urška; Lorber, Mateja; Bolha, Anja; Bahar, Jasmina Bevc; Lavrič, Miha; Turk, Sonja Šostar (Frontiers in Nutrition, 2025)
IntroductionVending machines offer a convenient way for food distribution, particularly favored by employees, students, and individuals seeking a quick snack. Food vending machines typically offer unhealthy, calorie-dense, and nutrient-poor options, which contribute to the rise of non-communicable diseases. Creating a healthier food environment is crucial, particularly in universities where students are developing their eating habits and becoming more independent. Key considerations for vending machines include the quality, nutritional value, and price of the products with a recent and growing attention toward sustainability.MethodsThe present study thoroughly examined 30 vending machines across 30 faculties in Slovenia. The analysis focused on assessing the variety and sustainability of the available products. The following was evaluated through three primary criteria, based on the information available on the product label: nutritional quality, environmental impact (palm oil content, packaging materials, and sustainability certificates), and socioeconomic indicators (suitability for people with special dietary needs).ResultsThe results revealed a low proportion of products met the proposed sustainability criteria, highlighting the need to promote sustainability in the vending machine industry. Although food categories like dairy products, fruits, and nuts have better nutritional profiles, they are underrepresented. In contrast, items like biscuits, crisps, snacks, and pre-prepared sandwiches often exceed recommended fat, salt, and sugar levels. More than one-quarter of products contained palm oil, only two were labeled as palm oil-free, and a limited proportion of products were suitable for individuals with special dietary requirements such as gluten sensitivity and lactose intolerance.DiscussionImproving the food selection in vending machines, guided by suggested sustainability criteria, presents a promising strategy for reshaping the food environment and promoting sustainable healthy diets, taking into account nutritional, environmental, and socioeconomic indicators.